The role of a tensile stress bias for a sensitive silicon mechanical stress sensor based on a change in gate-induced-drain leakage current - Lau, W. S. (2013)
Mechanical stress sensors based on silicon piezoresistance have limited sensitivity. Mechanical stress sensors based on the on-current or off-current or threshold voltage of silicon MOS transistors also have limited sensitivity. In this paper, we report that the sensitivity of a silicon-based mechanical sensor can be significantly improved by simply monitoring the gate-induced-drain leakage (GIDL) current of an n-channel MOS transistor. The role of a tensile mechanical stress bias will also be discussed.